Zhang Peili From Painting to Video - Krischer, Olivier (ANU Press, 2019)
In 2014, New York-based artist Lois Conner gifted one of pioneering Chinese artist Zhang Peili's last paintings to The Australian National University's newly opened Australian Centre on China in the World. Never exhibited and thought lost, the reemergence of Flying Machine (1994) prompts an exploration of the relation between painting and video in the oeuvre of Zhang Peili. Given Zhang's significance as a leading conceptual painter in the 1980s, then as a media art pioneer and educator in the 1990s and 2000s, Zhang Peili: From Painting to Video is also a nuanced study of broader developments in Chinese contemporary art's history. Featuring contributions by historian Geremie R. Barmé, photographer Lois Conner, art historians John Clark, Katie Grube, and Olivier Krischer, and curator Kim Machan, these essays together challenge the narrative of Zhang as 'the father of Chinese video art', highlighting instead the conceptual consistency, rigour, and formal experimentation in his work, which transcends a specific medium. By equal measure, the book embraces longstanding connections as integral to its meaning, connections between artists, curators and researchers, collaborators, colleagues and friends through China and Australia.